The Basic Principle Of The Man To Islam View - Ahdar Djamaluddin (Tadbir: Jurnal Manajemen Pendidikan Islam, 2016)
The constraint will be discussed in this paper in connection with the above title and background are as follows:1. How the principle that man is the noblest creatures in the universe.2. How the principle belief that the human body has three dimensions, namely, body, intellect and spirit.3. How the principle that human beings are affected by factors in the growth of heritage, natural environment, motivations and needs.The Qur'an confirms the quality and value of human beings by using three kinds of terms that are related to each other , al - insan al - Bechar and the sons of Adam . Given the human mind and heart , so as to understand the science of God sent down a Qur'an. With cultured human sciences afford . God created man in the best of circumstances should be drawing this ( At- Tin paragraph 4 ) . Human remains dignified noble if they are as caliph kept alive by God 's teachings . By karan in exaggerated human knowledge of other creatures . the human is a very noble creature of all beings in the universe , God blessed virtue that sets it apart from other creatures . God equips man with a few specific traits , with the gift of human beings entitled to respect from other creatures .Islam admitting human needs to the objects and the importance of the objects in human life , but the emphasis with aspect is very clearly nonsensical or spritual man should not live for the body alone , uncertain if he would go down commensurate animals . Require human intellect and spirit . His need to sense and spirit even more important . Between the body and the mind manifestation of this spirit , there should be no difference between the interests of these three aspects or between material interests and spiritual needs , because there is no obvious reason that hinders the interests and the need on each factor , the alignment even be the basis in Islam because it is not distinguished between objects or between body and soul mind and spirit .Undue physical growth always influenced by heredity . Personal growth and social tendencies are not always influenced by environmental factors at all, . Sometimes physical growth is influenced by environmental factors . Both naturally shaped like climate , season and soil properties Interchangeability , or socio - cultural nature such as how to eat , how to maintain the body from disease and treatment.